A medical physics review of the use of contrasodium in hysterosalpingography (HSG) examinations - Akbar, Aidil; Habib, Alltop Amri Ya; Simanjuntak, Asnika Putri; Emrinaldi, Tengku (Universitas Riau, 2025)
Hysterosalpingography (HSG) is a widely used radiological procedure for evaluating female infertility, particularly in assessing fallopian tube patency and uterine anatomy. A critical component of HSG is the use of contrast media. Water-based contrast agents, such as contrasodium, are often preferred due to their favorable safety profile. The field of medical physics plays a vital role in ensuring diagnostic image quality while minimizing biological risks from radiation exposure. This article reviews the effectiveness of contrasodium in HSG procedures from a medical physics perspective, comparing it to other contrast agents and examining radiation dose management in women of reproductive age. The study is a literature review of scientific publications from the past decade (2015–2024), including clinical trials, meta-analyses, and international guidelines from the WHO and ICRP. The analysis focuses on imaging physics parameters, contrast efficiency, biological safety, and radiation dose evaluation. Findings indicate that contrasodium provides sufficient radiological imaging with minimal biological risk. Although oil-based contrast agents are associated with higher post-HSG pregnancy rates, they pose greater risks of adverse biological effects. Medical physicists are instrumental in optimizing imaging protocols, managing radiation doses, and selecting exposure parameters in accordance with the ALARA (As Low As Reasonably Achievable) principle. In conclusion, the use of contrasodium in HSG offers an optimal balance between diagnostic efficacy and patient safety. The standardization of evidence-based HSG protocols at the national level is recommended to enhance clinical practice in Indonesia.